PENGARUH PERTUMBUHAN PENJUALAN, PERPUTARAN KAS, PERPUTARAN PIUTANG, DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN SUBSEKTOR MAKANAN & MINUMAN DI BURSA EFEK INDONESIA - I Gusti Ayu Kade Sri Wahyuniati; I Ketut Yudana Adi (Journal Research of Accounting, 2021)
Profit is one of the benchmarks for assessing the success or failure of company management. One of the ratios to measure profit is profitability. The profitability ratio used in this study is the Return on Assets (ROA). ROA shows the company's performance from the use of all its assets to generate profits. This study aims to obtain evidence of the effect of sales growth, cash turnover, accounts receivable turnover, and inventory turnover partially and simultaneously on ROA in food and beverage sub-sector companies on the Indonesia Stock Exchange. The population in this research were all food and beverage sub-sector manufacturing companies on the Indonesia Stock Exchange. The sampling technique used in this study was the purposive sampling method and obtained 10 companies. The analysis technique in this research uses multiple linear regression analysis techniques. The results of this research conclude that sales growth, cash turnover, and inventory turnover partially affect profitability. Meanwhile, accounts receivable turnover does not affect profitability. Simultaneously, sales growth, cash turnover, accounts receivable turnover, and inventory turnover affects profitability. The value of the coefficient of determination (Adjusted R Square) in this research is 0.683%, that's mean 68.3% of profitability is influenced by the variables tested in this research and the leftover is influenced by other variables outside of this research.